(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Based on the Human Development Index (HDI) figures, the Indonesian welfare level show that the community development process must be continuously carried out. The most important elements in the successful achievement of community development especially in rural community to support agricultural development are natural capital, technology, institutional, human capital, and social capital. The elements of social capital in this respect are mutual trustworthy on fellow members of the community, social empathy, social cohesion, social awareness, and collective cooperation. This paper examines the significance of social capital in agricultural development, as well as how the strategy to strengthening co-utilization and community development. Through a review of some study results on the role of facilitator in community development, strengthening social capital is required in the development community, particularly through the assistantship or mentoring process. Facilitators especially extension workers are needed in community development because of their function as problem analyst, group supervisor, trainer, innovator, and liaison officer. The principles of operation are (1) working group, (2) continuity, (3) self-reliance, (4) unity of target audiences, (5) growth of mutual trust, and (6) continuous learning process. In addition, the assistantship program is highly considered as an activity enabling the optimum empowerment of the poor. For an optimum role of technical assistant, the development of quality human resources is required through participatory training-based education and development of assistantship forum.